2016
DOI: 10.1021/acs.jmedchem.6b00071
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of 1-Methyl-1,4-dihydroindeno[1,2-c]pyrazole Analogues as Potential Anticancer Agents Targeting Tubulin Colchicine Binding Site

Abstract: By targeting a new binding region at the interface between αβ-tubulin heterodimers at the colchicine binding site, we designed a series of 7-substituted 1-methyl-1,4-dihydroindeno[1,2-c]pyrazoles as potential tubulin polymerization inhibitors. Among the compounds synthesized, 2-(6-ethoxy-3-(3-ethoxyphenylamino)-1-methyl-1,4-dihydroindeno[1,2-c]pyrazol-7-yloxy)acetamide 6a and 2-(6-ethoxy-3-(3-ethoxyphenylamino)-1-methyl-1,4-dihydroindeno[1,2-c]pyrazol-7-yloxy)-N-hydroxyacetamide 6n showed noteworthy low nanomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 52 publications
(103 reference statements)
0
54
0
Order By: Relevance
“…As the microtubule system plays a vital role in the maintenance of cell shape and basic cellular functions, an immunofluorescence staining assay was performed to study whether compound 28 could disrupt the microtubule dynamics in living cells 45 . 0.075 μM 28 moderately depolymerized interphase microtubules, whereas the depolymerization effect of 0.3 μM 28 is much stronger in MGC-803 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the microtubule system plays a vital role in the maintenance of cell shape and basic cellular functions, an immunofluorescence staining assay was performed to study whether compound 28 could disrupt the microtubule dynamics in living cells 45 . 0.075 μM 28 moderately depolymerized interphase microtubules, whereas the depolymerization effect of 0.3 μM 28 is much stronger in MGC-803 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the experiment showed that the effects of MMAE (EC 50 = 1.426 µM) on tubulin were reduced when the N-terminus was modified with the linkers (Cys-11-Cys-15: EC 50 = 1.525-2.903 µM), but this effect was relatively limited (Figure 2). All of the tested Cys-linker-MMAE conjugates produced concentration-dependent inhibition of tubulin polymerization, providing a basis for developing ADCs with Cys-linker-MMAE as potent payloads [27]. In addition, the results also show that the effect of linker length on the activity of the conjugate is weak, and the insertion of the p-aminobenzyl alcohol (PAB) structure in the linker does not significantly reduce its activity.…”
Section: Tubulin Polymerization Inhibition Studymentioning
confidence: 90%
“…DHPAC is a MTA that targets the colchicine binding site. 29 In previous studies, we did not investigate whether or not DHPAC can enter cells. In this study, we first used HPLC-MS/MS to assess whether DHPAC can enter cells.…”
Section: Dhpac Enters Cells and Inhibits Huvec Proliferationmentioning
confidence: 98%
“…DHPAC was obtained from the Institute of Medicinal Chemistry, School of Pharmaceutical Sciences, Shandong University. 29 Combretastain A4 (CA4) was purchased from Meilun Biotechnology Co, Ltd (Dalian, China). DHPAC and CA4 ( Figure 1A1,A2) were dissolved in dimethyl sulfoxide (DMSO) and stored at −20°C.…”
Section: Compoundsmentioning
confidence: 99%
See 1 more Smart Citation